(untitled) (Revista NUPEART, 2023)
The present text presents and analyzes the artistic and theore- tical bases that support the pedagogical action in the field of continuing education of art teachers and shares lived experien- ces in the compulsory subject "Theoretical Foundations of Art. in Education: contemporary contexts" that I offered to the class of 2021 as a Visitor Teacher at the Federal University of Paraíba. The text also presents the book "Doing, thinking and teaching performing arts: Epistemologies of the Far East of Brazil", a work in which a triple allusion is made: The first, to the expression Epistemologies of the South (Sousa Santos), as a metaphori- cal place in which groups of individuals were placed to remain silent, erased, diminished, despised and/or subordinated; the second, an allusion to João Pessoa, the city in which the Federal University of Paraíba is located; and the third, to the questions about the pertinence of the collection itself, indicating how, at times, we - artists, clowns and researchers of popular culture - are the one who place ourselves "in the South", when we erase and/or diminish ourselves as a reflection of the education recei- ved, from which the title of the article derives: We have a lot to relearn and unlearn!